STUDI KASUS PROTEKSI RADIASI PADA KONDISI KEGAWATDARURATAN PEMERIKSAAN PEDIATRIK PADA KASUS SUSP. EVENTRASIO DIAFRAGMA - Okzi Marsella; Ildsa Maulidya Mar’athus Nasokha; Fisnandya Meita Astari (JHN: Journal of Health and Nursing, 2026)
Radiation protection aims to safeguard patients by applying the principles of justification, optimization, and limitation, ensuring radiation doses remain as low as possible without compromising image quality. Pediatric patients exhibit high radiosensitivity because their body cells are actively developing, making them more susceptible to the biological effects of radiation. Pediatric emergencies often require rapid radiological examinations, such as in cases of suspected diaphragmatic eventration. Suboptimal use of exposure factors (kVp, mAs) and collimation settings can increase radiation doses received by pediatric patients. This study aims to describe the Entrance Surface Dose (ESD) values, analyze the influence of technical factors on ESD, and evaluate compliance with IAEA Diagnostic Reference Level (DRL) standards. A mixed-methods approach combining qualitative and quantitative methods was employed. The study subject was a 3-day-old pediatric patient undergoing an OMD (esophagogastroduodenal) examination during an emergency at the Radiology Department of Sleman Regional General Hospital (RSUD Sleman). Data were collected between September 2025 and June 2026 through observation and interviews with four informants: one radiologist, two radiographers, and one medical physicist; quantitative data were derived from Dose Area Product (DAP) values. The OMD examination involved five exposures—AP (first), AP (second), LPO, LPO (repeat), and RPO—resulting in a total ESD of 0.389 mGy. The total DAP was 508.7 mGy·cm², which remains below the IAEA DRL reference value of 760 mGy·cm² for the 0-year age group. Factors such as kVp, mAs, SID, and collimation area were found to directly influence ESD values. The use of a 42 × 42 cm collimation field was excessively large and suboptimal for a pediatric patient.